Foreign language training of higher education applicants philological profile in accordance with the EC (Pedagogy of Higher and Secondary Education, 2016)
Pobrezhnaya N. A. Foreign language training of higher education applicants philological profile in accordance with the EC.The article deals with the issues of foreign language training for specific purposes within the framework of European educational standards. The current means of foreign language training for specific purposes have been analyzed.The analysis of recent research and publications allowed us to clarify unresolved issues of of foreign language training for specific purposes. Of these, there are: the concept deficiency of intercultural foreign language education in different types of educational institutions; the lack of legal status of additional language education in specialized institutions; the inconsistency between the requirements of the Ministry of Education and the Council of Europe; the lack of standard curriculum of the discipline "Foreign language" for professional purposes at the level of state document.The potential possibilities for improving foreign language training for specific purposes according to European requirements have been scrutinized. The necessity of typical curriculum implementation of the discipline «Foreign language» for specific purposes has been substantiated. The standard curriculum with specialized language training content in teaching foreign languages as well as the evaluation criteria for the levels of foreign language knowledge must meet the existing international standards. The worldwide requirements for the level of foreign language proficiency in the academic and professional environments are measured with internationally recognized language exams such as ILEC (International Legal English Certificate), IELTS (International English Language Testing System) with academic purposes or FCE (Cambridge English: First). The target language level knowledge of graduating students should be defined according to international standards in the academic and professional environments.The adaptive model of foreign language training for professional purposes that meets the requirements outlined above can be represented conceptually as flexible connections between its components – objectives, content, organization of educational process and results. The terms of the foreign language training model for specific purposes are: gradual foreign language training, methodological support and system monitoring of foreign language training under the international language standards.
Keywords: foreign language training for specific purposes; European educational standards; language levels; standard curriculum; foreign language proficiency